AMPA Receptor Antagonist NBQX Decreased Seizures by Normalization of Perineuronal Nets - Chen, Wen; Li, Yan-Shuang; Gao, Jing; Lin, Xiao-Ying; Li, Xiao-Hong (PloS one, 2016)
Epilepsy is a serious brain disorder with diverse seizure types and epileptic syndromes. AMPA receptor antagonist 2,3-dihydroxy-6-nitro-7-sulfamoyl-benzoquinoxaline-2,3-dione (NBQX) attenuates spontaneous recurrent seizures in rats. However, the anti-epileptic effect of NBQX in chronic epilepsy model is poorly understood. Perineuronal nets (PNNs), specialized extracellular matrix structures, surround parvalbumin-positive inhibitory interneurons, and play a critical role in neuronal cell development and synaptic plasticity. Here, we focused on the potential involvement of PNNs in the treatment of epilepsy by NBQX. Rats were intraperitoneally (i.p.) injected with pentylenetetrazole (PTZ, 50 mg/kg) for 28 consecutive days to establish chronic epilepsy models. Subsequently, NBQX (20 mg/kg, i.p.) was injected for 3 days for the observation of behavioral measurements of epilepsy. The Wisteria floribundi agglutinin (WFA)-labeled PNNs were measured by immunohistochemical staining to evaluate the PNNs. The levels of three components of PNNs such as tenascin-R, aggrecan and neurocan were assayed by Western blot assay. The results showed that there are reduction of PNNs and decrease of tenascin-R, aggrecan and neurocan in the medial prefrontal cortex (mPFC) in the rats injected with PTZ. However, NBQX treatment normalized PNNs, tenascin-R, aggrecan and neurocan levels. NBQX was sufficient to decrease seizures through increasing the latency to seizures, decrease the duration of seizure onset, and reduce the scores for the severity of seizures. Furthermore, the degradation of mPFC PNNs by chondroitinase ABC (ChABC) exacerbated seizures in PTZ-treated rats. Finally, the anti-epileptic effect of NBQX was reversed by pretreatment with ChABC into mPFC. These findings revealed that PNNs degradation in mPFC is involved in the pathophysiology of epilepsy and enhancement of PNNs may be effective for the treatment of epilepsy.